Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s40104-015-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of thymol and carvacrol and their effects on broiler chickens challenged with Clostridium perfringens

Abstract: BackgroundIn the post-antibiotic era, essential oils (EO) are promising alternatives to growth-promoting antibiotics. The aim of the present study was to investigate the antibacterial activities of an EO product and its components thymol and carvacrol in vitro, and the efficacy of EO to control Clostridium perfringens challenge in broiler chickens.ResultsThe in vitro minimum inhibitory concentration assay showed strong antibacterial activity of the EO product, thymol, and carvacrol against pathogenic Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
104
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 47 publications
(78 reference statements)
20
104
3
2
Order By: Relevance
“…This aspect is also demonstrated in the use of carvacrol by optimizing other drugs to combat gastric cancer by improving the action of nanoparticles [12], as well as in stomach lesions decreasing infections that can progress to cancer [13]. As well as decreased metabolic activity in rat lymphoma with genotoxic action at high doses [14].…”
Section: Resultsmentioning
confidence: 99%
“…This aspect is also demonstrated in the use of carvacrol by optimizing other drugs to combat gastric cancer by improving the action of nanoparticles [12], as well as in stomach lesions decreasing infections that can progress to cancer [13]. As well as decreased metabolic activity in rat lymphoma with genotoxic action at high doses [14].…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study by Du et al (2015) found that carvacrol and thymol inhibited the growth of E. coli, Clostridium perfringens, and Salmonella strains. Gutierrez et al (2008) reported that in vitro, essential oils including basil, lemon balm, marjoram, oregano, rosemary, sage, and thyme, strongly inhibited the growth of B. cereus, P. aeruginosa, E. coli, and L. monocytogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol possesses several biological effects such as antibacterial, antioxidant, antitumor, anti-inflammatory and antifungal activities [93,94]. The antibacterial effects of thymol have been evaluated by several studies [95][96][97][98][99][100] against E. coli and S. typhimurium and the MIC values against these two strains was respectively MIC = 1 and MIC = 1.2 mM [95]. The antibacterial activity of thymol against S. typhimurium has been also studied by Palaniappan and Holley [97] and Chauhan and Kang [98], and the MIC values were respectively MIC = 2.5 mM and MIC = 750 mM.…”
Section: Thymolmentioning
confidence: 99%